Violencia intrafamiliar y su incidencia en las relaciones interpersonales de los jóvenes de la ciudad de Cariamanga, en el período actual - Vega Vega, Gloria Lesly (2024)
Domestic violence is an important social problem whose effects extend beyond the home and negatively affect the interpersonal relationships of young people. The present research work was carried out with the objective of analyzing domestic violence and its impact on the interpersonal relationships of young people, in the current period, as well as theoretically and methodologically substantiating domestic violence and its impact on interpersonal relationships and then identify causes and effects of domestic violence and its impact on the interpersonal relationships of young people in the city of Cariamanga; and finally, carry out social actions that reduce domestic violence and its impact on the interpersonal relationships of young people. The investigation was carried out in the city of Cariamanga specifically in the Central, La Fragua and La Merced neighborhoods over a period of three months. It was non- exploratory, cross-sectional, with a mixed approach, and a non-experimental design. The variables to be evaluated were domestic violence and interpersonal relationships in young people through the application of a survey, for which we worked with a sample of 218 young people from the Central, La Merced and La Fragua neighborhoods of the city of Cariamanga. To carry out the research, it was necessary to use a computer, Google Forms, and informed consent from the participants in this study. The results showed that the majority of people surveyed live in a healthy family environment, however, there is a small group of young people who experience situations of physical, verbal, sexual and economic violence, which affects their ability to establish relationships. interpersonal. In conclusion, this research served to thoroughly understand the problem of domestic violence and its impact on young people; Furthermore, the existence of domestic violence in some homes in the city of Cariamanga highlights the need for urgent intervention through strategies to educate and sensitize families about domestic violence.